2014
DOI: 10.1111/mve.12064
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mammal host diversity and density on the infection level of Trypanosoma cruzi in sylvatic kissing bugs

Abstract: Several reports have described host species diversity and identity as the most important factors influencing disease risk, producing either dilution or amplification of the pathogen in a host community. Triatomine vectors, mammals and the protozoan Trypanosoma cruzi (Trypanosomatida: Trypanosomatidae) Chagas are involved in the wild cycle of Chagas disease, in which infection of mammals occurs by contamination of mucous membranes or skin abrasions with insect-infected faeces. We examined the extent to which ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 29 publications
2
28
0
Order By: Relevance
“…Multiple studies have argued that high host diversity and low levels of anthropogenic disturbance tend to lead to lower intensities and prevalence of parasitism and disease in a wide range of systems (Keesing et al, 2010;Haas et al, 2011;Lacroix et al, 2014;Venesky et al, 2014), with vector-borne diseases in rodents being one important study system (LoGiudice et al, 2003;Friggens and Beier, 2010). However, other studies have failed to find a causal relationship (Giraudoux et al, 2013;Oda et al, 2014), or they have found idiosyncratic relationships across hosts, parasites, and environmental conditions (Froeschke et al, 2013;Salkeld et al, 2013;Young et al, 2013a;Kedem et al, 2014). Here, in contrast to other studies on fleas and flea-borne disease (Thamm et al, 2009;Friggens and Beier, 2010), we find no substantial support for a general effect of either disturbance or host diversity on frequency or levels of flea parasitism.…”
Section: Across Populationsmentioning
confidence: 99%
“…Multiple studies have argued that high host diversity and low levels of anthropogenic disturbance tend to lead to lower intensities and prevalence of parasitism and disease in a wide range of systems (Keesing et al, 2010;Haas et al, 2011;Lacroix et al, 2014;Venesky et al, 2014), with vector-borne diseases in rodents being one important study system (LoGiudice et al, 2003;Friggens and Beier, 2010). However, other studies have failed to find a causal relationship (Giraudoux et al, 2013;Oda et al, 2014), or they have found idiosyncratic relationships across hosts, parasites, and environmental conditions (Froeschke et al, 2013;Salkeld et al, 2013;Young et al, 2013a;Kedem et al, 2014). Here, in contrast to other studies on fleas and flea-borne disease (Thamm et al, 2009;Friggens and Beier, 2010), we find no substantial support for a general effect of either disturbance or host diversity on frequency or levels of flea parasitism.…”
Section: Across Populationsmentioning
confidence: 99%
“…Triatoma brasiliensis is found in different habitats in the Brazilian caatinga and cerrado environments (Valença-Barbosa et al, 2014) and Mepraia spp. are found in the Pacific coast of northern Chile, in the Atacama desert (Oda et al, 2014), both inhabiting rocks piles, among other different places. However, in the caatinga of Brazil, T. brasiliensis prefers wood accumulations to rock piles.…”
Section: Burned Rock Middens and Triatomine Insectsmentioning
confidence: 99%
“…Relating this to the IDI result, the significant effect detected may be caused by O. degus philopatric colony persistence in time and space, as what happens with vector colonies. P. darwini was the most abundant rodent species in the study site, highly infected with T. cruzi and a previous study documented that is one of the main blood sources for M. spinolai populations (Oda et al 2014). A. olivaceus was also highly infected, but it much less abundant.…”
Section: Discussionmentioning
confidence: 97%
“…1 Effects of the combined distance and colony prevalence (expressed as the infection distance index) on infection status. P positive, N negative) relatively high longevity and communal nursing (Previtali et al 2010), with potential vertical transmission of T. cruzi (Oda et al 2014), lead to a cumulative infection at the population level. Relating this to the IDI result, the significant effect detected may be caused by O. degus philopatric colony persistence in time and space, as what happens with vector colonies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation